Study the effect of Aqueous cold water and Alcoholic extracts of Ziziphus spina christi against bacteria isolated from Conjunctivitis In vitro and In vivo (Baghdad Science Journal, 2015)
This study aimed to study the effect of Ziziphus spina christi Aqueous cold and Alcoholic leaves and fruits extracts on the growth and activities of the following types of bacteria :( Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus pyogenes ). The results appeared outweigh the alcoholic extract of leaves and fruits of Sidr that prepared by saxholate extractor by addition of ethanol 95% significant superiority as compared with aqueous extract that prepared by using distilled water as was its influence inhibitor to the growth and effectiveness of bacteria , about the treatment of in-vivo to cause injury to these types of bacteria diagnosed laboratory mice and treated with alcoholic extract of the leaves of Sidr highest concentration of inhibitor Tests showed a positive response to treatment.